Evaluation of employees fruit consumption and its relation with Body Mass Index - Duarte, J. (2019)
The fruit intake in Portugal is below recommended levels despite evidence of the health benefits of regular consumption. Research indicates that there is an inverse relationship between fruit consumption and excessive weight. The workplace may be an ideal location for nutrition and health interventions, for example, in the context of occupational health, because of the potential health benefits for employees and associated decreases in absenteeism and sick leave. Employees spend a lot of their time at work which can represent a good setting for interventions to promote fruit consumption and weight control. The purpose of the present study was to evaluate the fruit intake status of employees and to examine the relationship between fruit intake and Body Mass Index (BMI).